Targeting cancer stem cells in hepatocellular cancer: a review - Khalid, Hina; Masoud, Muhammad Shareef; Qasim, Muhammad; Rahman, Mahmood-ur-; Ashfaq, Usman Ali (European Journal of Oncology and Environmental Health, 2015)
In connection with the self renewal property of stem cells, surprising similarities can be found in cancer cells. Tumors are composed of rapidly proliferating cells, postmitotic and differentiated cells. Since, however, the latter two types cannot self renew, the idea has arisen that tumors contain self renewing stem cells termed “Cancer Stem Cells” (CSCs) occupying the top of the cancer cell hierarchy. CSCs may have molecular signaling pathways responsible for self renewal as in stem cells. CSCs are often considered resistant to chemotherapy and targeting such cells and eradicating them may improve the prognosis of cancer patients. Hepatocellular carcinoma (HCC) is the sixth most diagnosed cancer, representing the second leading cause of world mortality and thought to be driven by CSCs. There are several antigenic markers and molecular signaling pathways such as Hedgehog, TGF-β, Wnt & Notch which modulate CSCs and account for tumorigenecity and hence progression of HCC. Additional factors such as micro-RNA may also contribute to hepatocarcinogenesis by regulating stemness of CSCs. Thus, understanding and characterizing the initiating CSCs and identifying the molecular targets will be helpful in preventing and treating HCC. Such molecular pathways and targets are discussed in this review.